IDENTIFYING COLONIAL LANDSCAPE STYLES IN BOGOR BOTANICAL GARDEN THROUGH VISITORS’ GEO-TAGGED PHOTOS - Hadi, Akhmad Arifin; Mizuuchi, Yusuke; Honjo, Tsuyoshi; Furuya, Katsunori (Badan Pengembang Konservasi UNNES, 2018)
The landscape of Bogor Botanical Garden (BBG) is influenced by different eras, particularly Dutch Colonial and post-war Indonesia. The research investigates visitors’ perceptions related to landscape of BBG based on visitors’ on-site experiences. The research involved 94 research participants, include local tourists and landscape architecture students. They were asked to take photo of landscape or elements they deemed colonial look landscape style using their own camera and send them online to researcher by social media. Each respondent were handed a GPS logger to record the capture locations of each photo. The results revealed that the most photos of colonial look landscape style were consist of buildings and hardscapes as focused objects, where Presidential Palace and Lady Raffles monument were buildings that mostly appear in photos. The photos’ captured locations were also concentrated to those buildings indicated that landscape surround those buildings had strong characteristics of colonial landscape style. The study also showed the effectiveness of inviting participants with educational background in landscape architecture than normal visitors to show perception of colonial look landscape on BBG site.